Dietary Mitophagy Enhancer: A Strategy for Healthy Brain Aging? - Nimmy Varghese; Selina Werner; Amandine Grimm; Anne Eckert (MDPI AG, 2020)
Recently, nutritional interventions have received attention as promising approaches to promote human health during a lifespan. The Mediterranean and Okinawan diets have been associated with longevity and decreasing risk for age-related diseases in contrast to the Western diet. The effect might be due to several antioxidative bioactive compounds highly consumed in both diets, namely, resveratrol, hydroxytyrosol, oleuropein, curcumin, and spermidine. This review aims to address the underlying mechanisms of these compounds to enhance mental fitness throughout life with a focus on brain mitophagy. Mitophagy is the autophagic clearance of dysfunctional, redundant, and aged mitochondria. In aging and neurodegenerative disorders, mitophagy is crucial to preserve the autophagy mechanism of the whole cell, especially during oxidative stress. Growing evidence indicates that curcumin, astaxanthin, resveratrol, hydroxytyrosol, oleuropein, and spermidine might exert protective functions via antioxidative properties and as well the enhanced induction of mitophagy mediators. The compounds seem to upregulate mitophagy and thereby alleviate the clearance of dysfunctional and aged mitochondria as well as mitogenesis. Thus, the Mediterranean or Okinawan diet could represent a feasible nutritional approach to reduce the risk of developing age-related cognitive impairment and corresponding disorders via the stimulation of mitophagy and thereby ensure a balanced redox state of brain cells.